Analysis of Musytarak Al-Lafdzi the Word “Kutiba” in the Qur'an: A Study of Semantic Analysis - Hima Roiku Dinia; Unzilatun Nikmah; Nur Ila Ifawati (Jurnal Studi Al-Qur'an, 2024)
The diversity of meanings in Musytarak lands in the Al-Qur'an is a challenge in the translation process, which causes ambiguity and the potential for multiple understandings if it needs to be translated or understood correctly. An example is lafadz, "kutiba," which has various meanings in the Qur'an that are very different from the original. This research aims to identify the meaning of the mustard lafdzi phenomenon, especially the lafadz “khutba" in the Al-Qur'an. This research is descriptive and qualitative using the literature review method. The data in this research comes from the Al-Qur'an, translations from several sources, and scientific works in relevant journals or books. The data was then analyzed descriptively to conclude a brief description. This research shows that Lafadz khutba is a lafa lafdzi repeated 11 times in the Koran and has several meanings. Lafadz kutiba means furidha (Required) found in Surah Al-Baqarah verses 178,180, 183, 216, 246, and An-Nisa' verse 77. Lafadz Kutiba means ju'ila (Made), found in Surah Ali Imron verse 154 and At-Taubah verses 120-121. The lafadz kutiba, meaning qudhiya (Determined or determined), is in Surah An-Nisa's verse 127 and Al-Hajj's verse 4. Thus, these results contribute to understanding the complexity of the meaning of "Kutiba" in the Al-Qur'an, emphasizing the importance of context in interpretation and translation to avoid misunderstandings.